Spatial Positioning of Gender in Two Award-winning Software Programs for Learning English: A Visual Content Analysis - Kordjazi, Zahra (BELT - Brazilian English Language Teaching Journal, 2014)
<!–[if gte mso 9]> 72 544x376 <![endif]–> This research was conducted to identify and interpret how spaces were differentiated by gender in visual images included in two award-winning English-learning software applications (Tell Me More and English at Home). The visual content analysis was based on examining the following values: home, workplace, street and neighborhood environment, leisure areas, and shop. Findings showed that females appeared as subordinate, financially dependent, and powerless; males as dominant, sporty, breadwinners, and powerful. Material writers, software developers, and instructors should be sensitized to such unfair positioning of gender and encouraged to promote alternative spatial discursive practices. Additionally, learners need to be well-informed and visually literate. It is argued that by discovering how females and males are positioned in contemporary interactive texts, consciously structured pictorial descriptions of gender can be articulated and contested in technology-based educational media to reflect gender equality. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>